ELUDASI KOMPLEKSITAS BIOAKTIF EKSTRAK MANGROVE (Rhizophora sp.) MELALUI METODE KROMATOGRAFI CAIR KINERJA TINGGI UNTUK KESEHATAN MANUSIA - Mishbach, Imam; Gea, Liyatin; Sujarta, Puguh; Tuhumena, Lolita Constantia; Ayer, Popi Ida Laila; Safaati, Sufeni (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background : Youtefa Bay, located in Jayapura City, Papua, is renowned for its natural beauty and is a conservation area with a mangrove forest ecosystem. The mangroves in Youtefa Bay, such as Rhizophora sp., play a crucial role in maintaining environmental balance and supporting the livelihoods of the surrounding communities. However, the biochemical complexity of these mangrove extracts poses a unique challenge in understanding their health effects. The objective of this research is to explore and elucidate the bioactive complexity of mangrove extracts, particularly Rhizophora sp. Methods: . The analytical method employed in this study is High-Performance Liquid Chromatography (HPLC). The results of this research show that Rhizophora sp. Results: Mangroves in Youtefa Bay, Jayapura City, contain various bioactive compounds such as alkaloids, flavonoids, terpenoids, saponins, and tannins, which are beneficial to health. Alkaloids aid in stimulating the nervous system, regulating blood pressure, and combating microbial infections. Flavonoids function as antibacterial and antioxidant agents, while terpenoids possess anti-inflammatory properties. Saponins are effective for the treatment of leukemia, asthma, rheumatism, and also exhibit anti-inflammatory effects. Tannins serve as anti-diarrheal, antioxidant, antibacterial, and astringent agents. Conclusion: Mangrove Rhizophora sp. has various active compounds which are very beneficial for health, so it is necessary to preserve the mangrove ecosystem in Youtefa Bay, Jayapura City.